High Expression of DEPDC1 Promotes Malignant Phenotypes of Breast Cancer Cells and Predicts Poor Prognosis in Patients With Breast Cancer - Zhao, Huishan; Yu, Mingwei; Sui, Laijian; Gong, Benjiao; Zhou, Bo; Chen, Jian; Gong, Zhaohua; Hao, Cuifang (Frontiers in Oncology, 2019)
DEP domain containing 1 (DEPDC1) is a novel tumor-associated and cell cycle related gene, which is aberrantly expressed in multiple types of cancer and involves in tumorigenesis and cancer progression. Here, we examined the functional involvement and underlying mechanism of DEPDC1 in breast cancer. In the present study, the immunohistochemistry results demonstrated that DEPDC1 was high-expressed in breast cancer tissues compared with the paired adjacent normal breast tissues, and its tendency at protein level was consistent with mRNA level from TCGA data. Moreover, DEPDC1 mRNA level revealed the strongest association with poor prognosis and development in breast cancer. In vitro assays showed that DEPDC1 overexpression resulted in significant promotion of proliferation by regulating cell cycle in MCF-7 cells, whilst an opposite effect was found in the MDA-MB-231 cells with DEPDC1 knockdown. Notably, further investigation indicated DEPDC1 promoted breast cancer cells migration and invasion ability. In addition, we discovered that DEPDC1 caused hyper-activation of PI3K/AKT/mTOR signaling in breast cancer cells. Therefore, the increased DEPDC1 expression in breast cancer is correlated to disease progression and poor survival, which suggested that DEPDC1 might be a potential therapeutic target against this disease.